Challenges in the Application of Genre Theory to Improve L2 Academic Writing: Effective Reports and Assessment - Maria Martinez Lirola; Derek S. Irwin (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
This paper examines the application of a systemic-functional linguistic (SFL) Genre Theory approach to an L2 classroom in Spain, where English systems and their formal and functional characteristics were explicated in the teaching-learning process in order to help students improve their writing skills. It analyses various facets of the effectiveness of this approach through a careful consideration of student report writing, first by analysing the assessors’ marking parameters and concentration, and second by thoroughly going through the papers themselves to summarise the nature and quantity of the various writing issues, paying particular attention to areas in which the existing assessment was questionable, incorrect, or not indicating errors in standard English.